Islamic Context on PISA-Like Mathematics Problem in Junior High School - Harisman Nizar; Agustiany Dumeva Putri; Liana Septy (Universitas Syiah Kuala, 2022)
This research was motivated by the low achievement of Indonesian students in the assessment of PISA problems and the Islamic context that is familiar to students. The purpose of this research was to produce valid and practical PISA-like mathematics problems using Islamic context in junior high school and to find out the potential effect of the problem on mathematical literacy ability. The subjects of this study were students of the Ninth grade in one of Junior High School, in South Sumatera, Indonesia.Furthermore, the methodology used was design research with the type of development study. The validity was obtained based on the assessment of the validator (expert) regarding the content, construct, and language used and student work in the one-to-one phase. Meanwhile, the practicality can be seen from the work of students in the small group phase where students can understand the meaning or language of the questions. Furthermore, the potential effect can be seen from the strategy of students in working on the questions during the field test. In this case, the potential effects that arise were mathematical communication ability, mathematical representation ability, and ability of devising strategies for solving problems, as well as mathematization ability.